The Effects of Leptin Hormone Concentrations and Some Immunological and Biochemical Parameters in Alloxan Induced Diabetic Male Rabbits and Diabetic Treated with Alpha Lipoic Acid and L-Carnitine - Mohanad Hasan Mahmood Humadi; Zaid Mohamad Mubarak; Ismat Jamal Jamil (Tikrit Journal of Pure Science)
This study was designed in order to estimate the effect of alloxan induced diabetes mellitus on leptin concentration and some immunological and biochemical parameters of male domestic rabbits. The study involved  (20) blood samples which divided into 4 groups : group one : adult normal healthy male rabbits as control group , group two: adult male rabbits with alloxan induced diabetes mellitus, group three: adult male rabbits with alloxan induced diabetes mellitus treated with alpha lipoic acid (100 mg/kg) , group four: adult male rabbits with alloxan induced diabetes mellitus treated with L-carnitine (100 mg/kg).The results of this study showed a significant increase in leptin concentrations (P≤ 0.05) of second group in comparison with control group; while significant decrease in leptin concentrations at levels (P≤ 0.05) of third and fourth groups compared with diabetic group, and there is significant increase in proinflammatory cytokine Interleukin 6 (IL-6) concentrations (P≤ 0.05) of second group in comparison with control group, There was a significant decrease in IL-6 concentrations (P≤ 0.05) of third and fourth groups in comparison with diabetic group; also there is a significant increases in both urea and creatinine concentrations (P≤ 0.05) of second group in comparison with control group,  while significant decreases in both urea and creatinine  concentrations (P≤ 0.05) of third and fourth groups in comparison with diabetic group.